Pattern Discovery Using K-Means Algorithm - Ahmed, AM; Norwawi, NM; Ishak, WHW; Alkilany, A (IEEE, 2024)
Student's placement in industry for the industrial training is difficult due to the large number of students and organizations involved. Further the matching process is complex due to the various criteria set by the organization and students. This paper will discuss the results of a pattern extraction process using a clustering algorithm that is k-means. The data use consists of Bachelor of Information Technology and Bachelor in Multimedia students of Universiti Utara Malaysia from the year 2004 till 2005. The experiments were conducted using undirected data and directed data. The pattern extracted gave information on the previous matching process done by the university.